The Attraction of the Enemy: A Computational and Cultural Evolutionary Approach to Polemical Rhetoric in Early Christianity - Špiclová, Zdeňka (Approaching religion, 2026)
This study investigates polemical representations of enemies in early Christian Greek literature (1-600 CE) through the framework of Cultural Attraction Theory. It begins with the identification of recurring categories of accusations—such as heresy, hypocrisy, arrogance, immorality, strife and associations with dubious characters—and, through a combination of close reading and extensive computational analysis of the GreLa corpus, finds that they exhibit both structural stability and diachronic transformation. Comparison with pagan corpora reveals shared reliance on Graeco-Roman rhetorical topoi, while also highlighting Christians’ increasing focus on heresiology after the Constantinian turn. The findings suggest that enemy depictions can be understood as cultural attractors, stabilized by cognitive mechanisms (such as negativity bias, moral disgust and categorization) and influenced by ecological factors (rhetorical conventions, persecution discourse, institutionalization and doctrinal consolidation).